2020
DOI: 10.12693/aphyspola.137.283
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties and Microstructure Development of Micro-Nano Fe/MgO Composite

Abstract: Micro-nano soft magnetic composite Fe/xMgO was prepared by press and sinter method. The microstructure and functional properties were investigated in dependence on particle size of MgO, as well as on MgO content ratio. Changes of electrical and magnetic properties were clarified on the background of the microstructure development. Particle size of the dielectric MgO phase significantly influenced the densification process, as well as the quality of insulation of each Fe particle from the others, hence the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A maximum in the coercive field is obtained as a function of the Fe and Co ion dopants (see Figure 5 ). Bures et al [ 53 ] also reported an increase of in Fe-doped MgO NPs for . Unfortunately, above this value there are no experimental data.…”
Section: Numerical Results and Discussionmentioning
confidence: 88%
“…A maximum in the coercive field is obtained as a function of the Fe and Co ion dopants (see Figure 5 ). Bures et al [ 53 ] also reported an increase of in Fe-doped MgO NPs for . Unfortunately, above this value there are no experimental data.…”
Section: Numerical Results and Discussionmentioning
confidence: 88%
“…With the increasing surface roughness of micron particles, it is necessary to use somewhat larger nanoparticles for perfect surface coverage, and at the same time the percolation threshold increases, as was shown in a previous study. 51…”
Section: ■ Discussionmentioning
confidence: 99%